The Effect of Capital Structure, Firm Age, and Gender Diversity on Financial Distress - Pahdia Nadira Dilla; Endrawati; Syafira Ramadhea Jr (Universitas Muhammadiyah Palembang, 2026)
The purpose of this study is to examine how capital structure, firm age, and gender diversity affect financial distress. The data were analyzed using a quantitative method with a purposive sampling technique for data collection. The data analysis technique employed was multiple linear regression, assisted by the STATA program. This study utilized data from 13 companies in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023.The study found that capital structure partially influences financial distress. Meanwhile, firm age, and gender diversity do not affect financial distress. This research is expected to assist companies in identifying early signs of financial distress, enabling them to take corrective action before it becomes critical, and to provide regulators with information for decision-making. Furthermore, this study can contribute to the development of knowledge in the field of accounting.